Предмет: Математика,
автор: gkrasucenko
решите пожалуйста
0,9(x-4) -3,3=0,6(2-x)
Ответы
Автор ответа:
1
0.9(x-4)-3.3=0.6(2-x)
0.9x-3.6-3.3=1.2-0.6x
0.9x+0.6x=3.6+3.3+1.2
1.5x=8.1
x=5.4
0.9x-3.6-3.3=1.2-0.6x
0.9x+0.6x=3.6+3.3+1.2
1.5x=8.1
x=5.4
gkrasucenko:
спасибки
Автор ответа:
0
Ответ:
5,4
Пошаговое объяснение:
0,9(х - 4) - 3,3 = 0,6(2 - х)
0,9х - 3,6 - 3,3 = 1,2 - 0,6х
0,9х - 6,9 = 1,2 - 0,6х
0,9х + 0,6х = 1,2 + 6,9
1,5х = 8,1
х = 8,1 : 1,5
х = 5,4
Похожие вопросы
Предмет: Русский язык,
автор: anita27072012
Предмет: Другие предметы,
автор: blackbublic
Предмет: Английский язык,
автор: vjwfhn
Предмет: Русский язык,
автор: dushess00